Stereoscopic particle image velocimetry for engine flow measurements: Principles and applications - El-Adawy, M. (Elsevier B.V., 2021)
There is an upsurge in the drive for better understanding of the processes, which control the combustion in modern engines. Large-scale intake generated flow structures, such as swirl and tumble, are known to have a significant effect on the combustion behaviour and have been widely studied by the automotive research community. Traditionally, the standard tools available to assess the in-cylinder flow behaviour inside an engine are either steady-state flow rigs or research engines with optical access. Steady-state flow rigs are used to evaluate the bulk motion using some integral parameters. Whilst the optical measurements are used to investigate detailed in-cylinder flow conditions. To assess the recent developments, principles and applications of stereoscopic particle image velocimetry to engine flow measurements are presented and discussed. Â© 2021 THE AUTHORS